Broadband‐emitting 2 D hybrid organic–inorganic perovskite based on cyclohexane‐bis(methylamonium) cation - Neogi, Ishita (2020)
A new broadband‐emitting 2 D hybrid organic–inorganic perovskite (CyBMA)PbBr4 based on highly flexible cis ‐1,3‐bis(methylaminohydrobromide)cyclohexane (CyBMABr) core has been designed, synthesized, and investigated, highlighting the effects of stereoisomerism of the templating cation on the formation and properties of the resulting perovskite. The new 2 D material has high exciton binding energy of 340 meV and a broad emission spanning from 380 to 750 nm, incorporating a prominent excitonic band and a less intense broad peak at room temperature. Significant changes in the photoluminescence (PL) spectrum were observed at lower temperatures, showing remarkable enhancement in the intensity of the broadband at the cost of excitonic emission. Temperature‐dependent PL mapping indicates the effective role of only a narrow band of excitonic absorption in the generation of the active channel for emission. Based on the evidences obtained from the photophysical investigations, we attributed the evolution of the broad B‐band of (CyBMA)PbBr4 to excitonic self‐trapped states.